Evidence for No Significant Impact of Müllerian Anomalies on Reproductive Outcomes of Twin Pregnancy in Korean Women. (16th February 2016) - Shim, Sohyun; Hur, Yoon-Mi; Kim, Da Hee; Seong, Seok Ju; Kim, Mi-La; Shin, Joong Sik
Abstract : The present article aimed to evaluate the impact of congenital Müllerian anomalies (MA) on twin pregnancy after 24 gestational weeks in Korean women. All records of twin pregnancies in a large maternity hospital in Korea between January 2005 and July 2013 were analyzed. Patients with monochorionic monoamniotic (MCMA) twins, non-Korean patients, patients with twins delivered prior to 24 gestational weeks, and patients with miscarriage of one fetus or intrauterine fetal death (IUFD) before 24 gestational weeks were excluded from data analysis. In total, 1, 422 women with twin pregnancy were eligible for data analysis, including 17 (1.2%) who had a known congenital MA (septate uterus, bicornuate uterus, arcuate uterus, and unicornuate uterus). Except for the mode of conception, baseline demographics were similar between women with MA and those without MA. No significant differences were found in pregnancy outcomes of gestational age at delivery ( p = .86), birth weight of smaller and larger twins ( p = .54 and p = .65), and number of twins with birth weight <5th percentile for gestational age ( p = .43).The rates of obstetrical complications such as pre-eclampsia, gestational diabetes mellitus (GDM), placenta previa, cerclage, IUFD, and postpartum hemorrhage were not significantly different between the two groups either. We concluded that the presence of congenital MA may not increase obstetrical risks in outcomes of pregnancy of twins delivered after 24 gestational weeks.